Domain Specific Concept Ontologies And Text Summarization As Hierarchical Fuzzy Logic Ranking Indicator On Malay Text Corpus - Shaiful Bakhtiar bin Rodzman; Normaly Kamal Ismail; Nurazzah Abd Rahman; Syed Ahmad Aljunid; Ahmad Yunus Mohd Noor; Zulhilmi Mohamed Nor (Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by SCOPUS